Do Universities Shape Their Students' Personality? - Stefanie Schurer; Sonja C. Kassenböhmer; Felix Leung (Institute for the Study of Labor (IZA), 2015)
We investigate whether universities select by, or also shape, their students' personality, as implied by the human capital investment model. Using a nationally representative sample of Australian adolescents followed over eight years, we find that youth conscientiousness, internal locus of control, and low extraversion strongly predict the probability of obtaining a university degree. However, university education does not shape those personality traits associated with a strong work ethic and intellect. Yet, it offsets a general decline in extraversion as individuals age and boosts the development of agreeableness for men from disadvantaged backgrounds. Our findings contribute to the discussion whether universities should teach their students broader skills.
Keywords: I12; J24; 330; university education; Big-Five personality traits; psychic cost; inequality; change in personality